Perioperative glycemic control and postoperative complications in patients undergoing emergency general surgery: What is the role of Plasma Hemoglobin A1c?. Issue 1 (January 2018) - Jehan, Faisal; Khan, Muhammad; Sakran, Joseph V.; Khreiss, Mohammad; O'Keeffe, Terence; Chi, Albert; Kulvatunyou, Narong; Jain, Arpana; Zakaria, El Rasheid; Joseph, Bellal
Abstract : BACKGROUND: Plasma hemoglobin A1c (HbA1c) reflects quality of glucose control in diabetic patients. Literature reports that patients undergoing surgery with an elevated HbA1c level are associated with increased postoperative morbidity and mortality. The aim of our study was to evaluate the impact of HbA1c level on outcomes after emergency general surgery (EGS). METHODS: We performed a 3-year analysis of our prospectively maintained EGS database. Patients who had HbA1c levels measured within 3 months before surgery were included. Patients were divided into two groups (HbA1c < 6 and HbA1c ≥ 6). Our primary outcome measures included in-hospital complications (major and minor complications), hospital and intensive care unit length of stay, and mortality. Secondary outcomes measures were 30-day complications, readmissions, and mortality. Multivariate and linear regressions were performed. RESULTS: Of the 402 study patients, mean age was 61 ± 12 years, 53% were females, and 63.8% were diabetics. Overall, 49% had an HbA1c ≥ 6%; the mortality rate was 6%. Those with hypertension, history of coronary artery disease, and body mass index of 30 kg/m 2 or greater were more likely to have HbA1c of 6.0% or greater. 7.9% patients experienced major complications. Patients with HbA1c of 6% or greater had a higher complication rate (36% vs 11%, p < 0.001) than those with HbA1c less than 6%. However there was no difference in mortality between two groups ( p = 0.09). After controlling for confounders, HbA1c ≥ 6.0% (odds ratio [OR], 2.9; p < 0.01) and a postoperative random blood sugar (RBS) of 200 mg/dL or greater (OR, 2.3; p < 0.01) were independent predictors of major complications. Patients with both HbA1c of 6.0% or greater and postoperative RBS of 200 or greater had higher odds (OR, 4.2; p < 0.01) of developing major complication. After adjusting for confounders, a higher HbA1c was independently correlated with a higher postoperative RBS (b = 0.494, [19.7–28.4], p = 0.02), but there was no correlation with the preoperative RBS. CONCLUSION: Patients with HbA1c of 6.0% or greater and a postoperative RBS of 200 mg/dL or greater have a four times higher risk of developing major complications after EGS. A preoperative HbA1c can stratify patients prone to develop postoperative hyperglycemia, regardless of their preoperative RBS. LEVEL OF EVIDENCE: Prognostic, level III.